Land surface temperature as potential indicator of burn severity in forest Mediterranean ecosystems - Quintano, C.; Fernández-Manso, A.; Calvo, L.; Marcos, E.; Valbuena, L. (International Journal of Applied Earth Observation and Geoinformation, 2015)
Forest fires are one of the most important causes of environmental alteration in Mediterranean countries. Discrimination of different degrees of burn severity is critical for improving management of fire-affected areas. This paper aims to evaluate the usefulness of land surface temperature (LST) as potential indicator of burn severity. We used a large convention-dominated wildfire, which occurred on 19–21 September, 2012 in Northwestern Spain. From this area, a 1-year series of six LST images were generated from Landsat 7 Enhanced Thematic Mapper (ETM+) data using a single channel algorithm. Further, the Composite Burn Index (CBI) was measured in 111 field plots to identify the burn severity level (low, moderate, and high). Evaluation of the potential relationship between post-fire LST and ground measured CBI was performed by both correlation analysis and regression models. Correlation coefficients were higher in the immediate post-fire LST images, but decreased during the fall of 2012 and increased again with a second maximum value in summer, 2013. A linear regression model between post-fire LST and CBI allowed us to represent spatially predicted CBI (R-squaredadj > 85%). After performing an analysis of variance (ANOVA) between post-fire LST and CBI, a Fisher’s least significant difference test determined that two burn severity levels (low-moderate and high) could be statistically distinguished. The identification of such burn severity levels is sufficient and useful to forest managers. We conclude that summer post-fire LST from moderate resolution satellite data may be considered as a valuable indicator of burn severity for large fires in Mediterranean forest ecosytems.
Keywords: burn severity; Composite Burn Index (CBI); Land surface temperature (LST); Landsat

Predicting the Recovery of Pinus halepensis and Quercus ilex Forests after a Large Wildfire in Northeastern Spain - Broncano, Maria José; Retana, Javier; Rodrigo, Anselm (Plant Ecology, 2005)
Quercus ilex and Pinus halepensis are two of the most common tree species of the western Mediterranean basin. Both species regenerate reliably after ﬁre: P. halepensis colonizes recently disturbed areas by eﬀective seedling recruitment, while Q. ilex resprouts vigorously after disturbances. For this reason, the natural regeneration of these species after ﬁre should ensure the re-establishment of a forest similar to that which existed before the ﬁre. This study analyzes with a simple simulation model whether or not the relative abundance of monospeciﬁc and mixed forests of these species in the landscape is altered by ﬁre. We also analyze the topographic factors and the forest structure before the ﬁre that determine the changes in forest composition after ﬁre. This study has been carried out in a large ﬁre that occurred in NE Spain. Overall, 33% of plots changed to another community type, but this probability of change varied considerably among community types before the ﬁre. Monospeciﬁc forests of P. halepensis or Q. ilex had a high probability of remaining in their original composition after the ﬁre, whereas the resilience of mixed forests of these two species was quite low. Mixed forests changed for the most part to monospeciﬁc P. halepensis or Q. ilex forests. Analysis of several factors determining these changes indicated that only elevation as a signiﬁcant topographical variable. The eﬀect of ﬁre was to increase the altitudinal diﬀerentiation between the two species. P. halepensis forests that changed to mixed or Q. ilex forests were those of highest elevation, while the mixed and Q. ilex plots that changed to P. halepensis forests were those located at the lowest elevations. Concerning structural variables before ﬁre, density of Q. ilex trees before the ﬁre showed a much greater eﬀect than P. halepensis density in determining the post-ﬁre community. Finally, burn severity also inﬂuenced the changes observed. For both P. halepensis and Q. ilex forests, plots that changed to another forest type were mainly those that burned more severely. In the case of mixed forests, even low ﬁre severities involved high probabilities of change to monospeciﬁc forests.
Keywords: burn severity; mediterranean forest; natural regeneration; post-fire recovery; resilience

Predicting the Recovery of Pinus halepensis and Quercus ilex Forests after a Large Wildfire in Northeastern Spain - Broncano, Maria José; Retana, Javier; Rodrigo, Anselm (Plant Ecology, 2005)
Quercus ilex and Pinus halepensis are two of the most common tree species of the western Mediterranean basin. Both species regenerate reliably after ﬁre: P. halepensis colonizes recently disturbed areas by eﬀective seedling recruitment, while Q. ilex resprouts vigorously after disturbances. For this reason, the natural regeneration of these species after ﬁre should ensure the re-establishment of a forest similar to that which existed before the ﬁre. This study analyzes with a simple simulation model whether or not the relative abundance of monospeciﬁc and mixed forests of these species in the landscape is altered by ﬁre. We also analyze the topographic factors and the forest structure before the ﬁre that determine the changes in forest composition after ﬁre. This study has been carried out in a large ﬁre that occurred in NE Spain. Overall, 33% of plots changed to another community type, but this probability of change varied considerably among community types before the ﬁre. Monospeciﬁc forests of P. halepensis or Q. ilex had a high probability of remaining in their original composition after the ﬁre, whereas the resilience of mixed forests of these two species was quite low. Mixed forests changed for the most part to monospeciﬁc P. halepensis or Q. ilex forests. Analysis of several factors determining these changes indicated that only elevation as a signiﬁcant topographical variable. The eﬀect of ﬁre was to increase the altitudinal diﬀerentiation between the two species. P. halepensis forests that changed to mixed or Q. ilex forests were those of highest elevation, while the mixed and Q. ilex plots that changed to P. halepensis forests were those located at the lowest elevations. Concerning structural variables before ﬁre, density of Q. ilex trees before the ﬁre showed a much greater eﬀect than P. halepensis density in determining the post-ﬁre community. Finally, burn severity also inﬂuenced the changes observed. For both P. halepensis and Q. ilex forests, plots that changed to another forest type were mainly those that burned more severely. In the case of mixed forests, even low ﬁre severities involved high probabilities of change to monospeciﬁc forests.
Keywords: burn severity; mediterranean forest; natural regeneration; post-fire recovery; resilience